Erhic – electron-proton collider with polarized beams - Berkaev, D.E.; Koop, I.A.; Otboev, A.V.; hatunov, Yu.M; Ptitsyn, V. (Вопросы атомной науки и техники, 2004)
The layout and main parameters of the e-ring for eRHIC project are presented. The optics properties to fulfill the so-called spin-transparency condition to obtain sufficient polarization degree at IP are given. The possibility of using super-bends for the polarization time in a wide energy range be decreased is also discussed.